Penilaian Risiko Keselamatan dan Kesehatan Kerja pada Area Packer di PT X Kota Palembang - Doeangge, Lala Febri Annissa; Noviadi, Pitri; Hendawati, Hendawati; Saputra T, Fider; Anwar, Khairil (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Palembang, 2025)
ABSTRACT Background: The bagging process in the cement industry has risks such as respiratory problems and eye irritation. The research objectives is to assess occupational safety and health risks in the packer area. Methods: This study uses a quantitative method with a descriptive design using questionnaire interview observation techniques. This research was conducted in February-May 2024, with a sample size of 10 packer area workers. Results: The characteristics of packer area workers at PT X are on average <50 years old, average education S1 and average work experience ≥10 years. The results of risk assessment research obtained chemical hazards and physical hazards with various risks, namely tripping, eye irritation, coughing silicosis, pinched, crushed, electric shock, explosion, fire, falling, deafness, dehydration, heat stress, wrist pain, neck and shoulder pain and back pain. From these activities, the risk rating is obtained, namely Extreme risk, High Risk and Medium Risk. Conclusion: Extreme risk activity is the operation of the cement packer equipment cleaning the cement shipping area. Keywords : Risk assessment, cement industry, packer area.